In situ 3D characterization of high temperature fatigue damage mechanisms in a cast aluminum alloy using synchrotron X-ray tomography. (1st March 2016) - Dezecot, Sebastien; Buffiere, Jean-Yves; Koster, Alain; Maurel, Vincent; Szmytka, Fabien; Charkaluk, Eric; Dahdah, Nora; El Bartali, Ahmed; Limodin, Nathalie; Witz, Jean-Francois
Abstract: Fatigue tests were performed at 250 °C on a cast AlSi7Cu3Mg aluminum alloy and monitored with Synchrotron in situ X-ray tomography in order to understand the micro-mechanisms of crack initiation and propagation. The analysis of the 3D images reveals that internal shrinkage pores are responsible for the main crack initiation. Crack propagation is mainly due to the complex and highly interconnected network of hard particles of the eutectic regions. Graphical abstract: